(untitled) (Asian Journal of Pharmaceutics (AJP), 2019)
Objective: The aim of the present work was formulation and evaluation of the ethosomal gel of tazarotene for topical delivery. Materials and Methods: Preparation of tazarotene-loaded ethosomes and gel base, optimization of ethosomes by varying criteria - lipid concentration, ethanol concentration, drug concentration, and stirrer time. The optimized formulation code found as F-13. Characterization of ethosomes performed by vesicle size, surface charge, entrapment efficiency, and stability study. Characterization of ethosomes containing gel performed by the measurement of viscosity, pH measurements, drug content, extrudability study, spreadability, and in vitro drug diffusion study. Results: Gel was prepared and evaluated for viscosity, % entrapment, extrudability, spreadability, and drug release study. It was found that viscosity of prepared gel EG-13 was 178.37 ± 5.07 cps, pH was 6.9, % assay was 97.57 ± 2.49, extrudability was 170 g, and spreadability (g.cm/sec) was found as 5.16 (g.cm/sec), respectively. In vitro drug release from ethosomes was studied using Franz diffusion cell method and found 76.65 ± 0.48% in 12 h. Drug release from ethosomal formulation was found in very sustained and controlled manner. Conclusion: It was concluded that prepared gel containing tazarotene-loaded ethosomal formulation was optimized and successfully formulated in the gel form can be of use for topical preparation for its antiacne affect.